Pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension: Technical challenges and controversies - Tom Verbelen, MD, PhD; Elie Fadel, MD, PhD; Christoph B. Wiedenroth, MD, PhD; David P. Jenkins, MS (Lond), FRCS (CTh); Michael M. Madani, MD, PhD (JHLT Open)
Chronic thromboembolic pulmonary hypertension requires referral to an expert center for final diagnosis and assessment of treatment possibilities by a multidisciplinary team. Pulmonary endarterectomy is the only potentially curative therapy and therefore remains the treatment of choice. However, many practices and minor technical aspects of this procedure may still provoke controversy. Based on the most recent literature and the author’s own experiences and opinions, and in lack of clear guidelines, this review discusses the rationale for blood management strategies; practices during deep hypothermic circulatory arrest; concomitant surgical procedures; pulmonary endarterectomy in specific patient populations, in redo setting and for other diseases; the role of balloon pulmonary angioplasty and of minimal access techniques; and the required surgical expertise. Well-founded recommendations can only be made for a few of them.